Impact of microclimate on the physiology, hair coat and milk production of dairy cows at different seasons - Santos, Laize Vieira; Carvalho, Cinara da Cunha Siqueira; Ruas, José Reinaldo Mendes; Diniz, Thamara Amaral; Silva, Edilane Aparecida da; Moreira, Sóstenes de Jesus Magalhães (Revista de Ciências Agroveterinárias, 2018)
The objective of this study was to evaluate the effects of the climatic environment on the physiological responses, changes in the hair coat and milk production of F1 Holstein and Zebu cattle from different maternal bases in two different seasons of the year. The study was conducted at the Experimental Farm of the Agricultural Research Company of Minas Gerais, in municipality of Felixlândia – Minas Gerais. Fifty dairy cows were evaluated in two seasons of the year (autumn and spring) for 21 days, with 25 animals evaluated in each season, belonging to 5 genetic groups, each group being composed of 5 animals. Daily measurements of air temperature and relative humidity were made using continuous reading dataloggers, at 10-minute intervals. The following physiological parameters were measured using a stethoscope, digital clinical thermometer and portable digital infrared thermometer: respiratory and cardiac frequency, body surface temperature and rectal temperature. Measurements were performed before and after milking in the morning and afternoon, daily in both evaluated seasons. The design was completely randomized in factorial scheme 5 x 2 (5 genetic groups and 2 seasons of the year). The variables were submitted to analysis of variance and, when significant to the F test, the means were compared by Tukey’s test at 5% of probability. There was no variation for most of the studied physiological parameters among the genetic groups, being higher during spring and in the afternoon (mean values: 33.2 breaths per minute, 79.4 heart rate per minute, 33.7 °C body surface temperature and 38.7 °C rectal temperature). The environmental variables in the two seasons of the year caused no changes in the productive responses of the animals (40.1 °C and 44.8 °C maximum air temperature and 95.4 and 96.0 maximum globe temperature and humidity index during autumn and spring, respectively), indicating the adaptation and resistance of F1 Holstein and Zebu animals.